2015
DOI: 10.3758/s13414-015-1011-5
|View full text |Cite
|
Sign up to set email alerts
|

Target selection biases from recent experience transfer across effectors

Abstract: Target selection is often biased by an observer’s recent experiences. However, not much is known about whether these selection biases influence behavior across different effectors. For example, does looking at a red object make it easier to subsequently reach towards another red object? In the current study, we asked observers to find the uniquely colored target object on each trial. Randomly intermixed pre-trial cues indicated the mode of action: either an eye movement or a visually guided reach movement to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…As a secondary point, the MRTs and SRTs both reveal bias toward the last target color, consistent with other research (e.g., Moher & Song, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…As a secondary point, the MRTs and SRTs both reveal bias toward the last target color, consistent with other research (e.g., Moher & Song, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, target selection biases observed in priming of popout or distractor-previewing effect can transfer across different types of actions (i.e. from an eye movement to a hand movement) [59,60]. These results suggest that selection biases are represented in memory largely independently from their associated actions.…”
Section: How Do Recent History and Future Anticipation Bias A Competition Of Action Plans?mentioning
confidence: 77%
“…Conversely, responses were faster if the distractors matched the previewed colour. This distractor-previewing effect has been also extended to saccades and reach target selection [58,59]. Furthermore, target selection biases observed in priming of popout or distractor-previewing effect can transfer across different types of actions (i.e.…”
Section: How Do Recent History and Future Anticipation Bias A Competimentioning
confidence: 88%
“…Furthermore, it has been suggested that movement goals for saccades and reaches are represented in separate brain areas of the posterior parietal cortex (Dickinson et al 2003). Other studies have reported a tight coupling between selection of targets for eye and hand movements (Gorbet and Sergio 2009;Moher and Song 2016; van Donkelaar 1997; see also Gopal and Murthy 2015). Moreover, overlapping brain activation has been observed in areas of the parietal and prefrontal cortex for eye and hand movement planning (Beurze et al 2009;Levy et al 2007), arguing against separate attentional systems.…”
Section: Introductionmentioning
confidence: 99%